Information technology for management : ongoing research and development : 15th Conference, AITM 2017 and 12th Conference, ISM 2017, held as a part of FedCSIS Prague, Czech Republic, September 3-6, 2017, extended selected papers /: ongoing research and development : 15th Conference, AITM 2017 and 12th Conference, ISM 2017, held as a part of FedCSIS Prague, Czech Republic, September 3-6, 2017, extended selected papers. (2018) - Unknown
No abstract available